Fictions of Desire Narrative Form in the Novels of Nagai Kafu - Snyder, Stephen (University of Hawaii Press, 2000)
Stephen Snyder examines Kafu's fiction in terms of narrative strategy, placing him squarely within some of the most important currents of literary modernism--at the nexus of Naturalism and the largely antithetical development of the modernist reflexive novel
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2021)
Keywords: LITERARY CRITICISM / Asian / Japanese; Japanese fiction -- 1868- -- History and criticism